Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 368184043 species occurrences available in GBIF matching the query: { "not" : { "RecordedBy" : [ "is not null" ] } } The dataset includes 368184043 records from 15901 constituent datasets: 15 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 1 records from The tadpoles of Murree Hills Frog Nanorana vicina (Anura: Dicroglossidae). 4 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 7 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 3 records from A new genus for the freshwater crab Potamonemus asylos Cumberlidgeı 1993 ı (Brachyura: Potamoidea: Potamonautidae) from Cameroonı Central Africaı with a key to the genera of the Potamonautinae. 3 records from MEXU/Leguminosae. 8 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 1 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 31 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 6191 records from marine sediment metagenome Metagenome. 3752 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 52873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 371 records from Bannwald Burghauser Forst. 1 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 5 records from The genus Litophyton Forskål, 1775 (Octocorallia: Alcyonacea: Nephtheidae) from Australia. 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 106 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 1 records from Nothrus pulverulentus. 2451 records from Macrobenthos Chukchi Sea, 1986. 5 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 49 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 1158 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 4739 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 1 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 48 records from Tardigrad collection of the National Museum of Nature and Science. 17301 records from Microbial community in marine sediments. 18 records from Naturtag. 5 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 5 records from A new sponge species of the genus Antho (Demospongiae, Microcionidae) from the Tyrrhenian deep Sea. 61000 records from Plant. 47 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 6 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 7 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 24 records from Chapter 7: Linnaean Plant Names and their Types (part Q). 1 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 91 records from Colecção Entomológica IIA. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 30070 records from 16S sequencing of environmental samples to test the impact of sediment source. 364 records from MZFC/Coleccion de Aves. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 3 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 5 records from Ostracods (Crustacea) associated with microbialites across the Permian-Triassic boundary in Dajiang (Guizhou Province, South China). 124 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 262 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 6 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 1990 records from Orthoptera - SMF. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 287870 records from Florida Keys Reef Visual Census 2014. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 2 records from BioGIS - Bryophytes - HUJ collections. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 50419 records from University of Michigan Museum of Paleontology - Vertebrates. 13 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 8 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 11 records from Herbarium Universitatis Daugavpiliensis. 5 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 672 records from Colección de Entomología - Curculionidae. 1 records from Universidad del Valle de Guatemala - Colección de Artrópodos. 6 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 2208 records from marine sediment metagenome Raw sequence reads. 18 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 2 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 2 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 55 records from Key to South American genera of Acanthocinini (Coleoptera, Cerambycidae Lamiinae) with erect setae on elytral surface. 35 records from Plecoptera. 3 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 1 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 4 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 4 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 1104 records from Swan Coastal Plain Survey. 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 114 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 4 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 8 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 8 records from NZCS Brownsberg Nature Park Monitoring. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 62122 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 2 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 1 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 2 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 120 records from BIRDRACE The early birds. 1289 records from RECORD Orthoptera Data. 7 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 1 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 1151 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF ARRAIAL DO CABO - BRAZIL. 115 records from Antarctic Pycnogonids II. 1181 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 255 records from ISM Ichthyology Collection. 2 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 18881 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 1863 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 765 records from National Museum of Natural Science. 23 records from A key to the species of Protogamasellus (Acari: Ascidae), with a new species from the Brazilian Pantanal. 1774 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 26 records from Results of a recent bat survey in Upper Myanmar including new records from the Kachin forests. 1084 records from Global Ocean Sampling Expedition. 69 records from BIRDRACE Pfeifenten. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 5335 records from Marine metagenome ICM_JRV. 40 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 213 records from Collections ichtyologiques et herpétologiques (BOUM). 7146 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 3 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 55 records from Temporary expansion to shelf depths rather than an onshore-offshore trend: the shallow-water rise and demise of the modern deep-sea brittle star family Ophiacanthidae (Echinodermata: Ophiuroidea). 1 records from Norwegian Lepidoptera working group. 7 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 52 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 6192 records from NE Scotland fish records 1800-2010. 300 records from Marine sediment metagenome ICM_GMS. 1 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 11 records from On the Bennelongia nimala and B. triangulata lineages (Crustacea, Ostracoda) in Western Australia, with the description of six new species. 3 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 4 records from bmhs_weatherheadshell_collection. 6 records from Sächsische Schweiz (Pfaffenstein). 47 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 31632 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 2 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 154 records from Living Cirripedia. 2 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 6695 records from Amundsen Gulf Overwintering Eukaryote Community. 1087 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 1 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 84 records from Roter Berg Werdau (Leubnitz). 5 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 3 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 7 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Wiese am Waldrand (Gurtweil). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 4976 records from Gastropod Specimens of the Yamagata Prefectural Museum. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 2 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 14069 records from Midden-Limburg Fish Ponds Survey. 108523 records from Herbarium Senckenbergianum (FR) - Fungi. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 209 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 18 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 133 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 5 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 578 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 154 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 2 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 10654 records from Bryophyte specimens of The Nagoya University Museum. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 2559 records from University of Guam Insect Collection. 39 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 9 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 174 records from Artenvielfalt des "Grünen Klassenzimmers". 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 754 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 2 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 1 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 2 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 4 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 289 records from UWIZM Molluscs. 272 records from MCP-Aves - Coleção de Aves. 2 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 824 records from Bird specimens of Saitama Museum of Natural History. 1 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 1 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 27 records from Collections of Bioclass, school #179, Moscow. 3 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 2226 records from pyrosequencing Raw sequence reads of deep-sea Archaea. 21809 records from Microbial community structure and dynamics in the oxygen minimum zone of the Northeast subarctic Pacific Ocean. 10 records from Mycology collection, Norwegian Forest and Landscape Institute. 24322 records from Muséum d'Avignon. 6 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 1 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 2 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 17 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 6 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 1 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 13 records from UWIZM Anoles. 3 records from New species of Alpinalona Alonso & Sinev, 2017 (Cladocera: Anomopoda: Chydoridae) from South-East USA. 2 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 1 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2257 records from Plant specimens of Bihoro Museum. 54 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 4193 records from Leicestershire and Rutland Aculeate Records. 5 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 10 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 2712345 records from First Bird Atlas. 79 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 1 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 20 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 394 records from Reptilia ZMK. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 4 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 1 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 21 records from Characterization of Microbial Community Structure and Population Dynamics of Tetrachloroethene-Dechlorinating Tidal Mudflat Communities using a Multipronged Approach. 19054 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 12888 records from MfN - Fossil Fish Collection. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 1785 records from 3Soil16S. 792 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 3 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 797 records from Variable Loading Conditions Influence Charge and Current Generation in Multi-Anode Environmental Microbial Fuel Cells. 15 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 1 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 237 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 76 records from BIRDRACE Nachtigallen. 1286 records from ConDidact Citizen Science Surveys - Amphibians 2007. 50 records from Occurrence of mammalia relicts at site Biedermann. 208 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 577 records from Lucanidae. 191004 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 1 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 408 records from Birds Specimens of Akita Prefectural Museum. 1 records from Delimiting the snapping shrimp Alpheus lobidens De Haan, 1849 (Caridea: Alpheidae) based on morphological and molecular data. 1 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 1 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 1024 records from MSUM Ichthyology and Herpetology Collections. 1 records from Juvenile eucladid crinoid from the Middle Devonian of Turkey. 7122 records from Whale catches in the Southern Ocean. 16809 records from Genebank, National Institute of Agrobiological Sciences. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 407 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 6 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 4 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 2 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 3145 records from PCE/TCE dechlorinating microbial community and dehalogenase genes from Wonju Stream, South Korea. 4 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 1 records from Great Eastern Ranges - Slopes to Summit. 9 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 20117 records from Tiroler Landesmuseum Ferdinandeum. 61 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 28 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 9 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 78 records from Mammals (GNHM-MM). 2 records from The first Cacomorphocerus species (Coleoptera, Cantharidae) from Rovno amber a second species of the genus with 11 - segmented antennae. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 6 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 26389 records from Protist Diversity in the East China Sea. 1715184 records from NBIS Records to December 2016. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 931 records from South American Antarctic Marine Biodiversity Literature. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 4 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 1 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 2 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 660 records from Collection Hydrozoa - ZSM München. 384 records from Marine metagenome ICM_AWP. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 66519 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 9056 records from NE Scotland other invertebrate records 1800-2010. 14 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 9 records from Review of the millipede family Haplodesmidae Cook, 1895, with descriptions of some new or poorly-known species (Diplopoda, Polydesmida). 2 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 6 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 10 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 697 records from 2019_NSMK_PL. 3 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 18 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 10 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 9 records from EDIT - ATBI in Gemer area (Slovakia). 22137 records from Global compendium of Aedes albopictus occurrence. 48 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 105 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 4 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 152 records from AKG-Gelände (Bensheim). 1 records from Occurrence of mammalia relicts at site Raagelund. 120 records from WOLL AVH data. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 2 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 210 records from Lebensraum Gesamtschule (Langerwehe). 283 records from Antarctic Amphipoda. 3 records from Discovery of the genus Micropeneta Pic in China, with description of a new species (Coleoptera: Tenebrionidae: Gnathidiini). 1 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 164 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 30 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 5 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 8 records from Revision of the Western Palae arctic species of the genus Casinaria H (Hymenoptera, Ichneumonidae, Campopleginae). 422150 records from NOAA AFSC North Pacific Groundfish Observer. 2568 records from Fish (NHMK-PI). 2 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 31150 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 40 records from makran-chabahar-arthropods. 6 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 4 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 169854 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 1 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 3 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 3 records from Herbarium specimens of Limoges university (LIMO). 128557 records from Fish specimens of Kagoshima University Museum. 15 records from UTEP Invertebrates (Arctos). 227 records from Diptera Collection of Museum and Institute of Zoology PAS. 66 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 59 records from Schulteich Freie Waldorfschule Darmstadt. 1 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 14 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 998 records from Korean Ethnobotany Database. 15 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 28 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 145 records from Foto trampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 258354 records from MGYS00005313. 81 records from CNIN/Abejas de México/Apoidea. 10 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 1 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 4 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 6 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 12 records from Art´n Vielfalt im Kinderwald. 150 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 4 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 302 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 27633 records from hymenoptera. 44826 records from Naturalis Biodiversity Center (NL) - Crustacea. 389 records from Amphibian and Reptilian (KIEE-AR). 25 records from Brown algae specimens of Komatsu City Museum. 1123 records from Danish Ants (Formicidae). 54 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 718 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 17 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 64 records from The Broward College Insect Collection. 23970 records from Berea College, Ralph L. Thompson Herbarium. 44 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 8 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 14 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 794 records from Isle of Wight non-native invasive species. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 6 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 581 records from Floristic records in the Moscow and Novgorod regions. 17 records from Marine metagenome ICM_AGW. 25 records from Weber State University Herbarium. 5 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 1 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 17 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 8 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 13 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 8 records from Die Bachspezies 2008/2009. 11 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 19 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 68 records from Streuobstwiese. 2 records from SIM-Fungal records compiled by Joan Montón. 6 records from Nueva especie de Aleuropleurocelus Drews y Sampson (Hemiptera: Aleyrodidae) y clave para especies del grupo de forma oval. 181529 records from Western Australian Museum provider for OZCAM. 1 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 234754 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 1 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 4 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 33 records from Waldstück am Schullandheim Bad Bederkesa. 7 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 8257 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 1 records from Berlese's Primitive Oribatid Mites. 200 records from Chapter 7: Linnaean Plant Names and their Types (part O). 6 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 5 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 30 records from NatureMap Calcrete Survey. 73 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 7 records from Taphonomy and environment of deposition of a juvenile tyrannosaurid skeleton from the Hell Creek Formation (latest Maastridhtian) of southeastern Montana. 431 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 22 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 3586 records from University of Minnesota Insect Collection. 29904 records from ARABEL - Arachnologia Belgica. 8112 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 83 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 23562 records from Arctic Species Trend Index (ASTI) : Marine. 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 348 records from Antarctic pycnogonids. 1 records from MLZ Bird Collection (Arctos). 2 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 17 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 4 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 5 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 954 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 24 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 724 records from There are 3 zooplankton samples from 3 different ponds, we collected sample and use the fresh samples to do DNA extraction directly, then mix them with adjustment guided by the number of species within each of them. At last, use Hiseq-2599 PE-150 to do NGS work. 2 records from A New Genus And Species Of Panaphantina (Coleoptera: Staphylinidae: Pselaphinae: Euplectitae: Trichonychini) From Australia. 46 records from An der Ohm, (Wettsaasen). 4 records from Two new species of heavily calcified cyclostome bryozoans from the intertidal of Akkeshi Bay, Hokkaido, Japan. 41 records from BioGIS - Vascular plants - Israeli Gene Bank. 14 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 260 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 40148 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 3 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 25446 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 759 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 1 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 17 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 825 records from Marine Turtles. 73 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 1247 records from Weeds Australia. 15 records from Conringia orientalis. 4 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 8 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 2 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 10 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1277 records from Vermont Orthoptera Records from Historic Dot Maps. 8 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 8 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 1412 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 101 records from Naturgrundstück (Eutin). 2 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 28 records from Korean Plant Virus Database. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 1 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 49 records from Herbarium Senckenbergianum (FR) - Protista. 9 records from Colección de helechos de la FML. 23 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 33 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 233 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 13 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 14 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 56 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1207 records from Microbial diversity studies of Arabian Sea sediment. 5055 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 1 records from Patterns of head shape and scutellation in Drymarchon couperi (Squamata: Colubridae) reveal a single species. 321 records from Echinoderms from the Seaflower Biosphere Reserve. 21 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 180126 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 77887 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 2 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 13 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 5 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 208 records from Chapter 7: Linnaean Plant Names and their Types (part V). 1480 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 8 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 10122 records from Uncultured eukaryotes Targeted Locus (Loci). 2 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 98 records from Warnowtal (Rostock). 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 16 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 9 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 2747 records from Compost microbe establishment and growth in agricultural soils. 202122 records from National Benthic Inventory. 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 111 records from BIRDRACE Die Wendehälse. 4 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 10 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 3 records from Utah State University, Intermountain Herbarium. 351778 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 223486 records from Phytochorologie des départements français. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 9902 records from DSMZ Bacteria. 27578 records from CAS Entomology (ENT). 25253 records from Naturalis Biodiversity Center (NL) - Pisces. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 7 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 2 records from Myxomycetes collection of the University of Eastern Finland. 11 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 1 records from Seasearch Marine Surveys in England. 27 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 8 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 834 records from What bug is that. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 1 records from Cretessenia roccamenaica nov. sp. (Acari: Prostigmata: Chyzeriidae: Chyzeriinae) from Sicily, Italy. 5 records from Five new species of the genus Noeetomima Enderlein (Diptera: Lauxaniidae) from China, with a key to world species. 13 records from Warnowufer Groß Klein. 21 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 5 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 19 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 14 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 1481 records from Leicestershire and Rutland Mature trees Inventory 2011. 1 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 6752 records from University of California Santa Barbara Invertebrate Zoology Collection. 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhingidae. 2 records from Neue Milbenarten aus Kärnten. 3 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 11 records from Entomology Collection at the Natural History Museum of Utah. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 2 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 185 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 24 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 1589 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 10003 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 503 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 2 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 59 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 2 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 807 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 1 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 1 records from Notes on and key to the genus Phengaris (s. str.) (Lepidoptera, Lycaenidae) from mainland China with description of a new species. 384 records from "Schwarzwassertal" bei Pobershau. 2041 records from marine metagenome Targeted Locus (Loci). 1 records from Occurrence of mammalia relicts at site Ejstrup. 2944 records from Plan de vertebrados de la Patagonia. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 2 records from Myzostoma khanhkhoaensis (Myzostomida), a new myzostomid species from the Nhatrang Bay, Vietnam. 3 records from Occurrence of mammalia relicts at site Igstadt I. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 199 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 975 records from Danielsberg (Mölltal, Kärnten). 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 232661 records from Oklahoma Vascular Plants Database Provider. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 148 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 31 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 11463 records from Liste des pays par taxon spécimen TOGO. 6977 records from 2019_NSMK_PL_2. 2073 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 2085 records from Foreign plant germplasm collections in Ghana. 1 records from Description of Pseudosteineria longisetis sp. n. from northeastern Brazil with a review of the genus Pseudosteineria Wieser, 1956 (Nematoda: Xyalidae). 328 records from UCYN-A diversity in the Pacific. 5 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 18 records from Fauna Species of Camiguin Island, Philippines. 10 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 23 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 31199 records from Collection Pisces SMF. 2691 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41553 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 3 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 120716 records from Microbial biogeography of 925 geothermal springs in New Zealand. 1 records from MEXU/Tipos de plantas vasculares. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 11 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 7 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 14 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 242 records from Landschaftspflegehof (Berlin). 5 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 10 records from Bachpatenschaft Beeke. 1 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 5 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 26 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 1863 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 48 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 3 records from Estonian Nature Observations Database. 12 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 43 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 715 records from Botanical Museum, Copenhagen, Mycology Herbarium. 589 records from Birds (NMNO-BI). 17713 records from NCSM Mammals Collection. 11 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 28 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 21 records from Riedkanal Bötzingen. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 3 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 31 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 14 records from Distribution of Aureoboletus projectellus in Europe. 445 records from Enrichment metagenome. 1057 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 22888 records from eDNA_Subseafloor. 10 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 2140 records from Captive Primate Specimens of Japan Monkey Centre. 30 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 7 records from A Catalogue and Historical Study of the Odonata of Ecuador. 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 3 records from A new fossil species of Pycnomerus Erichson (Coleoptera: Zopheridae) from Baltic amber, and a replacement name for a Recent North American congener. 5 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 4 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 1 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 1 records from A new species of Casmaria H. Adams & A. Adams, 1853 (Gastropoda, Cassidae) from the Philippines identified by molecular data. 1148 records from Analysis of plasmidome of high-altitude lakes from the Andean Puna. 5 records from Loricifera - SMF. 3 records from New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 1 records from Distoseptispora bambusae sp. nov. (Distoseptisporaceae) on bamboo from China and Thailand. 480819 records from KTP Ring Data. 14 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 14 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 119 records from Collection des mammifères d'Auvergne. 2 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 16469 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 1422 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 48 records from Morphologische Daten von Natrix. 4 records from Taxonomic revision of the epigean representatives of the spider subfamily Harpacteinae (Araneae: Dysderidae) on the island of Crete. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 26 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 1700 records from Brown University Herbarium. 95 records from BIRDRACE accipiter hardcore birding. 8 records from Key to the currently recognized species of Limnias Schrank, 1803 (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae). 71 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 19 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 11 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 315 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 1 records from A new species of Andinobates (Anura: Dendrobatidae) from the Urabá region of Colombia. 5 records from A review of Bennelongia De Deckker & McKenzie, 1981 (Crustacea, Ostracoda) species from eastern Australia with the description of three new species. 678 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 14 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 40 records from Annotated catalogue of the click-beetle tribe Senodoniini (Coleoptera: Elateridae: Dendrometrinae). 250 records from Hormigas del Museo de Entomología de la Universidad del Valle. 2 records from Macrocyrtus imomzodai Barševskis, 2016, a new synonym of Metapocyrtus (Orthocyrtus) orbiferoides Schultze, 1918 (Coleoptera: Curculionidae: Entiminae). 35 records from Reptiles Specimens of Akita Prefectural Museum. 2 records from Frenopyxis stierlitzi gen. nov., sp. nov. - new testate amoeba (Amoebozoa Arcellinida) from the urban parks with notes on the systematics of the family Centropyxidae Jung, 1942. 46 records from UWIZM Snakes. 155 records from Type material of land snails (Mollusca: Gastropoda) described from New Zealand by taxonomists in Europe and North America between 1830 and 1934, and the history of research on the New Zealand land snail fauna from 1824 to 1917. 9 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 7 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 1 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 14009 records from Collection Trichoptera - SMF. 8 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 33 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 255 records from Occurrence of mammalia relicts at site Raj Cave. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 84 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 163 records from Arizona State University Hasbrouck Insect Collection. 125 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 63364 records from CCAMLR historic KRILL. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 429 records from Collection Strepsiptera SMF. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 19 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 257 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 2 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 8 records from Abundant box jellyfish, Chironex sp. (Cnidaria: Cubozoa: Chirodropidae), discovered at depths of over 50 m on western Australian coastal reefs. 87901 records from MDFRC macroinvertebrate survey. 10 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 62 records from Amtsrain Apolda-Zottelstedt. 7 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 138 records from MoJ BioBlitz August 2018. 2 records from Gladiopycnodontidae, a new family of pycnodontiform fishes from the Late Cretaceous of Lebanon, with the description of three genera. 10 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 209 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 1 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 1 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 23 records from Catalogue of the Syrphidae of Egypt (Diptera). 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 139 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 62 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 99 records from Dorfrand Mauderode. 411 records from SuLaMa reptile survey I 2012. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 9 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 12093 records from K-State Museum of Entomological and Prairie Arthropod Research. 12 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 149 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 81 records from Marine benthic dataset (version 1) commissioned by UKOOA. 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 163 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 1 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 78 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 1 records from A new species of the assassin bug genus Rihirbus (Hemiptera: Heteroptera Reduviidae) from Vietnam. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 20 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 14 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 1000 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 1552 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 23 records from Landwehrbach. 8 records from Taxonomy and diversity of coelobite bryozoans from drift coral cobbles on Co To Island, northern Vietnam. 33 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 10079 records from CSIRO, fish surveys by the Soela, 1980s. 2 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 30004 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 6 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 12 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 46 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 4 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 1 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 4000 records from Fossil Specimens of Komatsu City Museum. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 3 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 3 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 363 records from PSUZC-Reptile Collection. 33 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3322 records from BioGIS - Mammals - SPNI. 18 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 2 records from SEWBReC Birds (South East Wales). 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 807 records from Área Galeras - Monitoreo de Aves, 2016. 83 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 1 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 5951 records from Collection Echinodermata SMF. 1 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 7 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 42702 records from MfN - Fossil vertebrates IV. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 33 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 5 records from MEXU/Flora de Oaxaca. 8598 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 9741 records from marine sediment metagenome Raw sequence reads. 9634639 records from Pl@ntNet automatically identified occurrences. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 3 records from Notes on Oriental Clivinini and the description of two new species (Coleoptera: Carabidae: Clivinini). 9304 records from Echinoderm collection of National Museum of Nature and Science. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 3191 records from Herps Specimens. 2420 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 1698 records from Red-throated diver national surveys in Scotland - raw data. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 2 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 2 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 16 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 118 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 696 records from the diversity of anammox bacteria in the subterranean estuary. 21 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 1 records from Arthropoden aus südostalpinen Höhlen.. 2 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 3812 records from Microbial communities associated with ferromanganese nodules and the surrounding sediments. 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 172 records from checklist-of-birds-of-zomba-mountain. 28007 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 998 records from Plant of Folklore (KIDR-PL). 9 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 7883 records from MfN - Fossil plants (Paleophytic). 2507 records from East Ayrshire Species Database. 1 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 1 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 3 records from Leif Richardson Vermont Bee Specimens. 8 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 29618 records from Collection Crustacea - ZMB. 1 records from A gall mite, Aceria rhodiolae (Acari: Eriophyidae), altering the phytochemistry of a medicinal plant, Rhodiola rosea (Crassulaceae), in the Canadian Arctic. 3 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 5 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 4 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 2 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 19 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 154 records from Dermaptera in the icipe collection. 9 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 60 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 57 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 109 records from MMFR Zingiberaceae Botanical. 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 10 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 533 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 10 records from Catalogue of Ampulicidae, Crabronidae and Sphecidae of Iran (Hymenoptera, Apoidea). 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 1 records from Seven new species of Night Frogs (Anura, Nyctibatrachidae) from the Western Ghats Biodiversity Hotspot of India, with remarkably high diversity of diminutive forms. 1 records from Brachiopods Specimens of Akita Prefectural Museum. 69 records from PRESENCIA DE VISÓN AMERICANO EN TIERRA DEL FUEGO, MAGALLANES, CHILE. 2421 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Tanacetum vulgare dominated forb vegetation. 3 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 430 records from Archaeal diversity of surface seawater (A3,A5,G3,G5) Targeted Locus (Loci). 176 records from Renaturierung Werse (Innenbereich Beckum). 4585 records from Marine bacteria Targeted Locus (Loci). 1 records from FUEL - Herbário da Universidade Estadual de Londrina. 280 records from Atlantic Forestry Centre Insect Reference Collection. 78684 records from Dataflos. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 11454 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 2743 records from marine sediment metagenome Raw sequence reads. 62 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 20191 records from Seabirds in Norway - Estimated population sizes. 4 records from A new scale insect host family (Hemiptera: Asterolecaniidae) for Aphytis (Hymenoptera: Aphelinidae) in China. 55 records from Occurrence of mammalia relicts at site Rusenschloß. 4 records from Is Copytus Skogsberg, 1939 (Crustacea: Ostracoda) a neocytherideid? With description of a new family and two new species. 4942 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 1469 records from Marine eukaryotes Targeted loci environmental. 2 records from Two new species of Spider Wasps (Hymenoptera, Pompilidae), Ctenagenia pagliano from Lebanon and Evagetes liane from Canary Islands. 69 records from The Amphibians of the Mitaraka massif, French Guiana. 3 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1653 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 817 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 2 records from Two new species of the genus Daptonema Cobb, 1920 (Nematoda: Xyalidae) found in an intertidal seagrass bed on the coast of the Andaman Sea, Thailand, with reference to the taxonomic status of the genus Trichotheristus Wieser, 1956. 301 records from Institut Mediterrani d'Estudis Avançats (CSIC-UIB): IMEDEA-OTO. 524 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 72399 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1199 records from Oxygen minimal zone Targeted loci environmental. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 74 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 1 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 2 records from Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate. 13 records from Lane 6 Analysis. 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 1 records from The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae). 153 records from VSN-Wiese. 3 records from Fourth note on the Dinosauria of the Laramie.. 3 records from New records of Chalcidoidea (Hymenoptera) from the Maltese Islands with an updated checklist. 6 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 7462 records from Ibaraki Nature Museum, Fungi collection. 303 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 781 records from Ecological study of the plankton in the port of Ostend in 1965. 22 records from Révision du genre Danuriella Westwood, 1889 (Mantodea). 384 records from Saltern microbial community diversity. 9 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 5 records from Intertidal Euryleptid polyclads and description of a new Stylostomum Lang, 1884 from Maharashtra, India. 15 records from The types of skippers described by Shu-Iti Murayama (Lepidoptera: Hesperiidae). 20442 records from Trondheim urban biodyversity survey. 10 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 985 records from Marine planktonic ciliates: SSU rDNA. 4579 records from Estación Biológica de Doñana - CSIC, Anfibios. 1 records from R. L. McGregor Herbarium Lichen Collection. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 9 records from Hybrizontinae (Hymenoptera, Ichneumonidae), a new subfamily for the fauna of Turkey. 71 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 2 records from New data on the taxonomy and distribution of Philippine Ochodaeidae and description of a new species from Central Visayas (Coleoptera: Scarabaeoidea). 66 records from Bird Specimens of The Cattle Museum. 557 records from Corn bunting breeding distribution in Scotland. 1 records from -- First- - description -- of- - the- - male- - of- - Dendrothrips karnyi (Thysanoptera, -- Thripidae) - from- - Iran. 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 27 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 4 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 9329 records from Centre de Ressources Biologiques de l'Institut Pasteur. 153 records from Selztal bei Friesenheim. 3453 records from Banded Iron Formation and Greenstone survey data. 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 1 records from Description of Walkeriella miraculosa, gen. n. et sp. n. from South-East Peru (Lepidoptera: Hepialoidea: Hepialidae). 9 records from A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti‘aro, Cook Islands, South Pacific. 8978 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 131 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 40 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1748 records from Floral visits on plants, InsectScale 2008. 2510 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 1170 records from Arizona State University Vascular Plant Herbarium. 6 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 1496 records from Stoneworts in Wales. 2 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 169600 records from Plant niche rather than soil or species shapes the microbiota. 1 records from Contribution to the knowledge of the Neotropical canopy dwelling genus Onorius (Coleopteraı Scarabaeidaeı Orphninae): another species from southern Ecuador and notes on the hind gut morphology in the Orphninae. 4570 records from Biogeography of near-shore reef fishes in northern New Zealand. 1 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 37 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 19 records from Four subgenera of Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) newly recorded from China, with description of five new species. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 6929 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 2 records from NE AVH data. 2174 records from ConDidact Citizen Science Surveys - Snails 2006. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 2 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 48 records from Schulgelände (Wetter). 282 records from Deponie Klausdorf. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 961 records from Erlengraben/Lipp-Tal (Östringen). 22817 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 1480 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 756 records from Mokihinui and Karamaea small tributaries and seeps. 2 records from Aspilanta new genus (Heliozelidae) specimen data. 4 records from On the types species of the New World dung beetle genus Canthidium Erichson, 1847 (Coleoptera: Scarabaeidae: Scarabaeinae), with an annotated checklist of species. 16 records from Orthoptera (Tettigoniidae and Acridoidea) from Miombo woodlands of Central Tanzania with the description of new taxa. 1 records from Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species. 1548 records from Royal British Columbia Museum Entomology Collection. 122 records from Taxonomic revision of West African cone snails (Gastropoda: Conidae) based upon mitogenomic studies: implications for conservation. 1355 records from Antarctic Lakes Brine Raw sequence reads. 2 records from Four new species and new records of the Neotropical genus Alloraphes Franz (Coleoptera: Staphylinidae: Scydmaeninae). 29 records from Occurrence of mammalia relicts at site Großes Schulerloch. 28 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 13 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 27 records from Eight new Lepadellidae (Rotifera, Monogononta) from the Congo bring to level endemism in Africa’s rotifers. 266 records from Morphologische Daten von Puffinus creatopus. 23648 records from WTSWW Data: All Taxa (West Wales). 3 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 421246 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 214459 records from South Australian Museum Australia provider for OZCAM. 14 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 3 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 2 records from Brock University Herbarium (BU). 7208 records from Whicher Scarp Flora Survey. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 1 records from Diverse mechanisms of feeding and movement in Cyclorrhaphan larvae (Diptera). 191 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 58 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 8 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 12 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 37 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 20 records from Occurrence of mammalia relicts at site Niederlehme. 1 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 2366 records from Cryoconite sediments Targeted Locus (Loci). 19 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 43 records from UWIZM Cnidarians. 11 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 22059 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 40339 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 17 records from Surface samples of the NW Pacific Ocean Targeted Locus (Loci). 2664 records from Tasmanian Museum and Art Gallery provider for OZCAM. 6 records from TTRS Mammals. 123 records from Occurrence of mammalia relicts at site Veternica. 3 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 21 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 1001 records from Mushroom (KIDR-MR). 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 10 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 1 records from Genetic and morphological evidence for cryptic species in Macrobrachium australe and resurrection of M. ustulatum (Crustacea, Palaemonidae). 6 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling at Pathogen Plots]). 1 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 13 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 1199 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Occurrence of mammalia relicts at site High Furlong. 344 records from University of Sindh Jamshoro Herbarium. 53 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 19 records from Marine metagenome ICM_CNE. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 467 records from Bryozoa, Brachiopoda and Entoprocta from the collection of the Arctic University Museum of Norway in Tromsø. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 4 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 2 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 165 records from Registros Primates Neotropicales Convocatoria APC. 13 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 48 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 631 records from Anammox bacteria in sediment cores of Daya Bay, China. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 1 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 1 records from Hoplophora ardua. 1 records from Memecylon pseudomegacarpum M. Hughes (Melastomataceae), a new species of tree from Peninsular Malaysia. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 1 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 1 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 10 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 6 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 5 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 1 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 7 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 486 records from LISU Herbario Angola. 4687 records from nhmc_ob_2019. 3303 records from CNAC/Coleccion Nacional de Acaros. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 1217 records from 16S rRNA metagenomic investigation of arsenotrophic bacteriome of ground water and soil from arsenic-prone area of Bangladesh. 4 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 59 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 207 records from BioAcoustica: Wildlife Sounds Database. 3 records from Notes on the taxonomy of some “ Astaena ” species described by Burmeister (Coleoptera: Scarabaeidae: Melolonthinae). 3 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 22771 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 5 records from Contributions to the knowledge of Atlantic Canadian Histeridae (Coleoptera). 18 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 201 records from Biodiversity of springs and rock seepages 2003. 10776 records from CEFS_16S_ITS. 36323 records from Biowide Species data. 20 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 3 records from Mabuia wirzi Roux, 1925 (Squamata: Scincidae), an overlooked synonym of Dasia olivacea Gray, 1839, with notes on the synonymy of Dasia olivacea. 15 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 1 records from Protozoa ZMK. 521 records from Schanzenanlage Bergham. 2 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 1 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 35 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-025. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 5 records from Two new species of nematode (Oxyurida, Hystrignathidae) parasites of Passalus interstitialis Escholtz, 1829 (Coleoptera, Passalidae) from Cuba and a new locality for Longior similis Morffe, Garcia & Ventosa, 2009. 595 records from Free-living plathelminthes of marine habitats near Wimereux (1990-1991). 24 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 241 records from Amphibian Specimens of the Yamagata Prefectural Museum. 18 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 444 records from Marsabit Ecosystem Inventory Surveys 2014. 3 records from Dactylogyrids (Monogenea) parasitic on marine fish from Peru including the description of a new species of Haliotrema Johnston & Tiegs, 1922 and two new species of Parancylodiscoides Caballero & C. & Bravo-Hollis, 1961. 4 records from A taxonomic review of the genus Asterostegus (Echinodermata: Ophiuroidea), with the description of a new species. 2 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 561 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 9 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 59 records from Schulgelände SGD/Viersen. 66 records from Entomological collection of the National Museum. 144 records from BIRDRACE Punkbirder Helgoland. 1 records from Miriapodi di alcune grotte della Campania. 1 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 8 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 1212 records from BES pyrosequencing. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 61 records from Naturpark Kottenforst-Ville 15.6.09. 9 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 14 records from Two new free-living nematode species of Setosabatieria (Comesomatidea) from the East China Sea and the Chukchi Sea. 10 records from Lepidepecreoides stoddartae sp. nov. from the Falkland Islands (Amphipoda: Tryphosidae). 7 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 173 records from FFH-Gebiet Klosterwasser/Burkau. 55 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 3 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 386 records from Thistle Heads and Ermerged Insects. 32 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 1 records from Schulman's Neotropical Adelobotrys database. 12094 records from Amino acid addition experiment Metagenome. 1 records from An interesting new genus of Berothinae (Neuroptera: Berothidae) from the early Eocene Green River Formation, Colorado. 77 records from Colección Herpetológica de la Patagonia. 4 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 1 records from Description of a new species of genus Trachischium with a redescription of Trachischium fuscum (Serpentes: Colubridae: Natricinae). 55 records from Vegetationsmatrix schorfheide alb 2008 durchgang2. 3 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 48476 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 2268 records from Amplicon sequencing of gyrA and parC in Escherichia communities in river/lake sediments. 1288 records from Comparative metagenome analysis of normal and arsenic contaminated soils from ballia district, Uttar Pradesh, India. 771 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 4 records from A new species of Enosis Mabille, 1889 (Lepidoptera, Hesperiidae, Hesperiinae) from southern Brazil and notes on Enosis angularis (Möschler, 1877). 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 9349 records from Harriet Irving Botanical Gardens (HIBG). 46580 records from Weed and native flora data for the Swan Coastal Plain. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 889 records from 16S rRNA gene pyrosequencing and clone library revealed highly diverse microbial communities in natural marine biofilms. 2 records from Description of a new brachypterous scarab species, Orphnus brevialatus (Coleoptera: Scarabaeidae: Orphninae) from East Africa, with notes on flightlessness in the orphnines. 37 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 2293 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 4717 records from Weddell Sea macrozoobenthos EASIZ I. 2526 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 916 records from IOW Natural History & Archaeological Society Marine Records. 15 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 5 records from Contribution to the knowledge of the genus Cordilura Fallén (Diptera, Scathophagidae) from Japan, with descriptions of three new species. 14 records from Occurrence of mammalia relicts at site Climauti II. 10389 records from Seawater metagenome Targeted loci environmental. 135 records from Waldi-Weiher. 13 records from A reappraisal of the California Roach / Hitch (Cypriniformes, Cyprinidae, Hesperoleucus / Lavinia) species complex. 470 records from Gewann Krampf (Heilbronn). 1 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 1029 records from Circumpolar Seabird Monitoring Plan. 4 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 51 records from Visual Plants (144.41.33.158) - Private collection of Asta Napp-Zinn. 3340 records from Palaeobiology collection, FAU Erlangen. 6 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 2572 records from seawater metagenome Metagenome. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 3537 records from ATCC Bacteria Collection Catalog. 4372 records from Heliconiine Butterfly Collection Records from University of Cambridge. 1 records from Hemichordata collection of National Museum of Nature and Science. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 79 records from Birdrace-Bielefinken-Bielefeld. 7446 records from Fish specimens of Toyama Science Museum. 107 records from Müritz-Nationalpark. 297 records from Colección Limnológica Universidad de Antioquia. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 3 records from Current status of the non-indigenous molluscs in Chile, with the first record of Otala punctata (Müller, 1774) (Gastropoda: Helicidae) in the country and new records for Cornu aspersum (Müller, 1774) and Deroceras laeve (Müller, 1774). 95 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 272 records from Wald am Schloss Wittgenstein Bad Laasphe. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 1080 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 20 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 1 records from A new stenochirid lobster (Crustacea, Decapoda, Stenochiridae) from the Early Jurassic of France. 27108 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 10 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 3 records from The Mastigitae genus † Baltostigus in Upper Eocene Rovno amber (Coleoptera: Staphylinidae: Scydmaeninae). 1723 records from Tucurui_Metagenoma_MGRAST. 9577 records from Lepidoptera specimen database of Japan. 2499 records from Leicestershire and Rutland Reptile Records to 2011. 6 records from A review of fossil Bursidae and their use for phylogeny calibration. 5640 records from Solenosmilia matrix annotations and VME habitat identification in video from voyage IN2018_V06, Australia (2018). 27124 records from Collection Vermes - ZMB. 1448 records from Culture Collection of Algae. 130 records from BIRDRACE - The famous Grouse feat. The James. 33 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 1 records from Description of a new genus and two new species of Forsteriini Tippmann, 1960 from Peru (Coleoptera, Cerambycidae, Lamiinae). 1 records from Baetis pentaphyllus sp. nov., a new species of mayfly (Ephemeroptera: Baetidae) from the Russian Far East. 5 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 144 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 9 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 3 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 52 records from Occurrence of mammalia relicts at site Goyet Cave 3. 18 records from Schulgarten der Gesamtschule Am Heidberg. 68483 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 24795 records from Université d'Aix-Marseille. 4 records from MfN - Micropaleontology. 9 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1036 records from BUND - Dassower See (Lübeck/Dassow). 352 records from Birds and plant species near Petushki town (Vladimir region). 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 28 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1433 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 571 records from Cuxhavener Küstenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 1616778 records from Hatikka Observation Database. 1 records from A new Atheta species from the West Caucasus and a redescription of A. brevapicalis (Coleoptera: Staphylinidae: Aleocharinae). 1 records from Synopsis of the extinct Batrachia, Reptilia and Aves of North America. 5039 records from inatura - Erlebnis Naturschau Dornbirn. 7 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 42 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 2020 records from Birds (NHMK-BI). 2 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 3792 records from Sea water microorganisms Raw sequence reads. 5162 records from PlutoF platform observations. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 3 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 302 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 14 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 3 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 8066 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 5335 records from Database of invertebrates collected in Mongolia. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 23 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 32916 records from Insect specimen database of Atsugi City Museum. 72 records from Nematoda of Costa Rica (INBio). 74 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 4 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 31 records from NZCS Invertebrates New Collection After 1987. 1 records from A new species of the subgenus Troginus Mulsant et Rey 1878 (Coleoptera: Staphylinidae: Oxytelinae: Carpelimus) from Borneo. 2 records from Waidelotinae, a new subfamily of Pyrochroidae (Coleoptera: Tenebrionoidea) from Baltic amber of the Sambian peninsula and the interpretation of Sambian amber stratigraphy, age and location. 54 records from Colección nacional de palmas de Colombia - JBQ. 993 records from ROC RSPB Farmland Species Survey Dataset. 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 182049 records from Florida Keys Reef Visual Census 1999. 27810 records from Collection of saproxylic and xylobiont Beetles. 9 records from Steinbock (1937) Turbellaria XIV. The fishery grounds near Alexandria. Notes and Memories of the Fisheries Directorate of Egypt, No. 25. 46 records from Phenological Center - Mushrooms (Karelia). 10 records from Occurrence of mammalia relicts at site Meiendorf. 1146 records from Tachinid Recording Scheme - GB and Ireland records. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 6 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 2 records from A review of bat research in Thailand with eight new species records for the country. 5904 records from Canadian Museum of Nature Palynology Collection. 41 records from The Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) of Nepal. 44 records from The Sphecid Wasps of the genus Cerceris L, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from the Palearctic Region (part II). (Hymenoptera, Apoidea, Crabronidae). 7 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 1 records from New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam. 5 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 2 records from Osteology and relationships of Libanopycnodus wenzi gen. et sp. nov. and Sigmapycnodus giganteus gen. et sp. nov. (Pycnodontiformes) from the Late Cretaceous of Lebanon. 55 records from Galls on Beech Trees in Hainich, 2008. 5 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 2 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 1751 records from Microbial communities in deep eastern Mediterranean Sea surface sediments. 28 records from Lectotype designations, taxonomic notes and new synonymies in some species of the bee genus Centris Fabricius, 1804 described by Amédée Lepeletier de Saint-Fargeau (Hymenoptera: Apidae). 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 9 records from Cybaeus (Araneae: Cybaeidae): the adenes species group of the Californian clade. 1 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 1 records from Arthropoden aus südostalpinen Höhlen.. 185 records from New species of Ilanga (Gastropoda: Trochoidea: Solariellidae) from the Indo-West Pacific. 1 records from Ctenophora ZMK. 9 records from Studies in Mexican Grasshoppers: A new species of Pedies Saussure (Acrididae: Melanoplinae) with comments on the unusual blue coloration on the abdomens of females and live specimen images for three other congenerics. 85 records from Diversification in the mountains: a generic reappraisal of the Western Ghats endemic gecko genus Dravidogecko Smith, 1933 (Squamata: Gekkonidae) with descriptions of six new species. 500 records from Chronicle of Nature - Phenology of Insects of Pechoro-Ilych State Nature Reserve. 4 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 3 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 1 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 6 records from Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea.. 2 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 1114 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 3 records from Tyrannosaurs suffered from gout. 244 records from Quarrendorfer Landschaftsschutzgebiet. 23 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 2 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 6 records from Dryinidae and Embolemidae (Hymenoptera, Chrysidoidea) from Anijima, Ogasawara Islands, Japan. 30 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 3 records from Settling the name Diomedea exulans Linnaeus, 1758 for the Wandering Albatross by neotypification. 9225 records from Equatorial Pacific Ocean Targeted loci environmental. 387039 records from Swiss National Databank of Vascular Plants. 40135 records from DIBA-Parc del Montnegre i el Corredor. 2 records from Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids. 26 records from JRS Wetands data Rwanda, 2019. 1 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 145 records from Cepario de Microorganismos y Hongos Filamentosos de la Universidad del Valle. 7 records from Grundwasserlebensraum im Englischen Garten (München). 1 records from Review of the genus Bythonia Oman 1936 with description of a new species and new record from Venezuela (Hemiptera, Cicadellidae, Iassinae). 3 records from Herbario de la Sociedad Micológica Barakaldo Mikologia Elkartea. 16 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 1 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 8 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 34 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 409 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 137 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 386 records from MCP - Coleção de Abelhas. 26 records from Erhard Sopp. 857 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 5 records from New state records of lady beetles (Coleoptera: Coccinellidae: Coccinellinae) from Missouri and Mississippi, USA. 5 records from SCFS - Sagehen Herbarium. 10 records from New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia). 1 records from A new African species of Stenichnodes (Coleoptera: Staphylinidae: Scydmaeninae). 437 records from Bird specimens of Bihoro Museum. 17 records from Aglaotilla, a new genus of Australian Mutillidae (Hymenoptera) with metallic coloration. 2 records from Wie viel Natur gibt es im Park?. 964 records from Freshwater Fishes of Bulgaria. 2 records from Genetic evidence supports Sylvilagus mansuetus (Lagomorpha: Leporidae) as a subspecies of S. bachmani. 1823 records from Colección de Anfibios. 3 records from A new species of Bicoxidens Attems, 1928 (Diplopoda, Spirostreptida, Spirostreptidae) from northern Zimbabwe. 4 records from Seodaemun Museum of Natural History Fossil. 26 records from NBMB Herps. 310 records from Umgebung der Gesamtschule Hamburg-Winterhude. 70 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 4 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 14 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 60 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 7805 records from University of Michigan Museum of Zoology, Division of Birds. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 2203 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 8 records from Redescription of Chrysidea pumiloides Zimmermann, 1956, and description of three new species of Chrysidea from Madagascar (Hymenoptera: Chrysididae). 1050 records from Collection Graptolithina fossil SMF. 1 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 268 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 7 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 4 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 52 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 5 records from The endemic Southern African genus Epirinus Dejean, 1833 (Coleoptera: Scarabaeidae: Scarabaeinae) revisited: five new species and two new synonyms. 62 records from Zoo Frankfurt. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 1 records from An XXL-CT-scan of an XXL Tyrannosaurus rex skull. 1 records from A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from the foothills of the Serranía Yariguíes of Colombia (Crustacea: Decapoda: Pseudothelphusidae). 1085628 records from Fungal Records Database of Britain and Ireland. 3 records from Revision of the genus Psorus Bergroth, 1914 (Hemiptera: Pentatomidae: Discocephalinae). 17 records from Systematics, Morphology and Biogeography Phylogeny of the Augochlora clade with the description of four new species (Hymenoptera, Apoidea). 74 records from A new species of the Liolaemus alticolor - bibronii group (Iguania: Liolaemidae) from East-central Argentina. 22 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 85658 records from Collection Aves (bird skins) SMF. 4 records from Revision of Arcastes Baly, 1865 from the Oriental Region (Coleoptera, Chrysomelidae, Galerucinae). 78 records from New taxa of the tribe Meconematini from South-Pacific and Indo-Malayan Regions (Orthoptera, Tettigoniidae, Meconematinae). 25 records from Taxonomic revision of the genus Probolomyrmex Mayr, 1901 (Hymenoptera: Formicidae: Proceratiinae) for the Neotropical Region. 1 records from Nymph inadvertently described as new species for a fourth time? On the identity of Euscelimena hardi (Tetrigidae: Scelimeninae) with general remarks on the identification of pygmy grasshopper nymphs. 4 records from Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India. 147 records from JOI - Herbário Joinvillea. 20 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 6 records from A revision of the African wolf spider genus Amblyothele Simon. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 84 records from BIRDRACE Vogelscheuchen. 2 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 2 records from Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA). 6 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 1 records from Zur Kenntnis der Lithobiiden. 2 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 2 records from Phasmarhabditis bonaquaense n. sp. (Nematoda: Rhabditidae), a new slug-parasitic nematode from the Czech Republic. 53 records from Leopard and Weddell seal program 1999/2002. 21 records from Collembola Poduromorpha from two littoral areas of northern Rio de Janeiro Brazil. 6827 records from Natural History Museum Maastricht (NL) - Herbarium. 393 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 149 records from MZL Invertebrate Collections. 1 records from New look on the geographical variation in Rhinolophus clivosus with description of a new horseshoe bat species from Cyrenaica, Libya. 1303 records from Crustacean specimens of Bihoro Museum. 9 records from New genus and species of cockroaches from the tribe Brachycolini (Blattaria Blaberidae: Blaberinae) and redescription of the Hormetica strumosa. 8195 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 5 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 1 records from Karpfenteich, Klasse 6d. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 9 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 1 records from Wrong side of the leaf: assigning some Lithocolletinae species (Lepidoptera: Gracillariidae) to their proper genera. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 5576 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 3435 records from Benthos Chirnov Basin 1986 and 2002. 529906 records from Queensland Museum provider for OZCAM. 4 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 3 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 9399 records from 16S rRNA amplicon from marine Bacteria Raw sequence reads. 101 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 1 records from Molche in Ruschwedel. 13 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 127 records from Freshwater crustaceans in Antarctic and sub-Antarctic lakes. 2 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 6 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 74 records from Review of the genus Paramesius Westwood, 1832 (Hymenoptera: Diapriidae, Spilomicrini) from Russia, with description of four new species. 263 records from Redland City Council Citizen Science Portal. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 12 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 5 records from COI mtDNA barcoding and morphology for species delimitation in the spider genus Ixchela Huber (Araneae: Pholcidae), with the description of two new species from Mexico. 2184 records from Spatial variation of bacterioplankton in south Atlantic Bight. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 296 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 2 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 16118 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 1 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 2 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 104 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 4 records from (UTC) University of Tennessee Mammals Collection. 13545 records from Temporal dynamics of bacterioplankton community in response to excessive nitrate loading in the oligotrophic coastal water. 2150 records from Birds Specimens. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 6 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 86 records from Fliegenhaupt Marksuhl. 1 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 2199 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 98 records from Occurrence of mammalia relicts at site Rejtek 1. 4 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 18 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 39 records from Bats of northeastern Vietnam. 2 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 5 records from Cryptic species among bumblebee mimics: an unrecognized Hemaris hawkmoth (Lepidoptera: Sphingidae) in eastern North America. 5 records from First record of the genus Dictyopharina Melichar, 1903 (Hemiptera: Fulgoroidea: Dictyopharidae) from China, with descriptions of two new species. 18 records from Taxonomic Accounts With Notes On Spatial Diversity And Relative Abundance Pattern Of Horseflies (Diptera: Tabanidae) From Sonamukhi Protected Forest Area Of West Bengal, India. 51 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 1 records from A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India. 116 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 23449 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 240 records from Knechtweide (Kohlfurth). 6336 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 1584 records from MCP-Mamiferos - Coleção de Mamíferos. 228 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 11 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 5 records from New biogeographical makeup for colonisation of the Baja California Peninsulaı with the description of a new Onthophagus (Coleoptera: Scarabaeidae: Scarabaeinae). 1113 records from Occurrence database of native plants and animals of south-central Chile. 14 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 3 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 181 records from Zambian Bat Collections Worldwide. 466 records from PSU-Seagrass Collection. 2 records from Hangzhou-sediment-sample Raw sequence reads. 2 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 3 records from Vascular plants of south-central China. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 4 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 19 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 3 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 96 records from BioGIS - Reptiles - HUJ collections. 5 records from An overview of the genus Plesionika Bate, 1888 (Decapoda, Caridea, Pandalidae) in Asian waters. 18525 records from Flora Atlas N.T.. 5216 records from E1 Targeted Locus (Loci). 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 5449 records from Fishes in the Argentine Sea from 1967 to the present time. 43 records from Herbario COFC de la Universidad de Córdoba: colección histórica. 35 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 3 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 9 records from REVISÃO DO GÊNERO “ LEPTOCYSTA ” STAL (Hemiptera, Tingidae). 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 25 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 1856 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 12 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 1 records from A new genus and species of burrower bugs (Heteroptera: Cydnidae) from the mid-Cretaceous Burmese amber. 2 records from Review of the Australian Signal Flies of the Genus Microepicausta (Diptera: Platystomatidae). 580 records from Rare plants database extract from Scottish Natural Heritage. 68377 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 7 records from Formidabel; Belgian Ants Database. 5 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 20 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 2 records from A new species of Globicornis Latreille (Coleoptera: Dermestidae) from Baltic amber, with a key to fossil species. 16604 records from CAS Invertebrate Zoology (IZ). 1 records from A new African Apiocera species (Apioceridae, Diptera). 5917 records from Antimony contaminated sediments Raw sequence reads. 5515 records from water Raw sequence reads. 17 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 14 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 16 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 12826 records from Community structure of Archaea in the western North Pacific and the Arctic Ocean. 1271 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 5 records from A new leafhopper genus Discolopeus and nine new species (Hemiptera, Cicadellidae, Deltocephalinae) associated with shrubs, trees and poisonous plants in South Africa. 30 records from Skull anatomy and phylogenetic assessment of a large specimen of Ecteniniidae (Eucynodontia: Probainognathia) from the Upper Triassic of southern Brazil. 1 records from A new tyrannosaurine (Theropoda: Tyrannosauridae) from the Campanian Foremost Formation of Alberta, Canada, provides insight into the evolution and biogeography of tyrannosaurids. 28 records from The first species of Cotithene Voss (Coleoptera: Curculionidae: Curculioninae) from Amazonian Brazil, with notes on its role as a pollinator of Evodianthus funifer (Poit.) Lindm. (Cyclanthaceae). 36 records from NSW South Coast & ACT plants. 6 records from Ascidians collected during the Madibenthos expedition in Martinique: 2. Stolidobranchia, Styelidae. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 714 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 1 records from Occurrence of mammalia relicts at site Ballybetagh. 6 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 210 records from Colección Ornitológica de la Universidad del Valle. 585 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 22 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 76 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 2 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 7 records from Untangling convoluted taxonomy of Chambriella Rego, Chubb & Pavanelli, 1999 (Cestoda: Proteocephalidae), with erection of Riggenbachiella n. g. and the description of a new species from pimelodid catfishes in the Neotropical Region. 372 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 374 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF GORGONA ISLAND. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 499 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 4 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 21 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 4 records from Indian Hecalina (Hemiptera: Cicadellidae: Deltocephalinae: Hecalini) with description of three new species. 797966 records from NatureServe Network Species Occurrence Data. 41676 records from Tagged Seal Location Data from SOGLOBEC. 310556 records from Dry Tortugas Reef Visual Census 2010. 1 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 26 records from Cetaceans sighted off the west coast of the South Island, New Zealand, Summer 1970. 4 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 28 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 28 records from On the morphology of the astragalus and calcaneus of the amphicyonids (Carnivora, Mammalia) from the Paleogene of Europe: implications for the ecology of the European bear-dogs. 1 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 3 records from Three new species of Oxypoda from Spain, Armenia, and Ukraine with notes on the fauna of Armenia (Coleoptera: Staphylinidae: Aleocharinae). 43 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 38 records from The Calliphoridae (Diptera) of Armenia. 5 records from Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay.. 12 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 66164 records from Florida Keys Reef Visual Census 1996. 114 records from Pollichia Pilzherbar. 175 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 3 records from Revision of the types of species of Alloxysta described by Cameron and Fergusson (Hymenoptera: Figitidae: Charipinae) and deposited in the Natural History Museum (London), including a key to the fauna of Great Britain. 13 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 1 records from Review of the leafhopper genus Longicornus Li & Song (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species. 74441 records from Wild bees of Belgium. 4 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 81 records from Birdrace-Die_Ornithomaten-Herford. 917 records from Área Galeras - Monitoreo de Aves abril-octubre, 2018. 1 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 341 records from NINA Vanndata fisk. 103 records from Mammals (UWEP-MM). 26 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 6 records from New species of the genera Havelockia and Thyone (Echinodermata: Holothuroidea) and first record of T. crassidisca from the southwestern Atlantic Ocean. 62 records from Artenvielfalt in der Kinderakademie im RFZ. 25 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 1 records from Notes on the grasshopper genera Longgenacris You & Li, 1983 and Fruhstorferiola Willemse, 1922 (Orthoptera: Acrididae: Melanoplinae) with proposal of a new synonym. 3275 records from Trawl-survey data from the “expedition Hvar” in the Adriatic Sea (Mediterranean) collected in 1948-1949. 53062 records from British Antarctic Survey Argos satellite tracking data. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Alcedinidae. 3 records from Contribution to the taxonomy of the paper wasp genus Polistes (Polistella) (Hymenoptera: Vespidae: Polistinae) from Vietnam, with description of a new species. 2108 records from BCCM/MUCL Fungi. 1 records from Zetes pallidulus. 1 records from A new jellynose, Ateleopus edentatus, from the western Pacific Ocean (Teleostei: Ateleopodiformes: Ateleopodidae). 230880 records from Soil bacterial diversity is associated with human population density in urban greenspaces. 19 records from A review of Synegiodes Swinhoe, 1892 (Lepidoptera: Geometridae), with description of two new species. 5149 records from Municipal Pensacola Beach Sand Metagenome. 600 records from Growth and age across range extension region of Centrostephanus rodgersii in eastern Tasmania and morphometric comparison of urchins inhabiting kelp versus barrens habitats, Australia (2004-2005). 3 records from Visual Plants (144.41.33.158) - Private collection of Barbara Kueppers. 5 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 12 records from Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan. 48 records from Freiheitsring (Frechen). 2 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 6992 records from Stone-curlew Annual Surveys. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 4 records from On the identity of Sternosternus grouvellei Guillebeau, 1894 (Coleoptera: Hydrophilidae, Phalacridae). 2 records from Taxonomic review of the genus Wasmannia.. 1 records from A new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the northern Western Ghats, Maharashtra, India. 2 records from Tamdamaeus staryi gen. nov., sp. nov. (Acari, Oribatida, Damaeidae) from Vietnam, with remarks on certain unusual diagnostic features. 25 records from Carnarvon Basin wetland survey. 2369 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 1 records from New genera and species from the Belly River Series (mid-Cretaceous). 35 records from South American Coccinellidae (Coleoptera), Part XIX: Overview of Cryptognathini and systematic revision of South American Cryptognatha Mulsant. 1 records from A revision of the Costa Rican species of Stenoeurilla Brailovsky & Barrera (Hemiptera: Heteroptera: Coreidae: Stenoscelideini), with the description of two new species, new distributional records, synonymical note, and key to the known species. 1 records from Revision of Sinonereis Wu & Sun, 1979 (Annelida: Nereididae). 265 records from Luderbusch. 2 records from Lyalinus, a new genus of Cneorhinini from Burkina Faso (Coleoptera: Curculionidae). 82 records from Teich im Wald zwischen Böblingen und Schönaich. 2504 records from Collections data on ecology of bottom animal of the Southern ocean. 2 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 1 records from DNA barcoding reveals a species group of the genus Campiglossa (Diptera, Tephritidae, Tephritinae) with recognition of a new species from East Asia and previously unknown females of Campiglossa coei (Hardy). 11 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 1369 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 18058 records from Fish Collection of Yokosuka City Museum. 2 records from Malawi-Cicindelidae-Biodiversity-Data. 1 records from Garra sindhi, a new species from the Jebel Samhan Nature Reserve in Oman (Teleostei: Cyprinidae). 1966 records from Global database of alien macrofungi. 13 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 7 records from Arizona State University Lois B. O'Brien Collection. 52 records from Occurrence of mammalia relicts at site Zigeunerfels. 4 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 80 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 2 records from Revision of Japanese species of Nipponomyia Alexander, 1924 (Diptera, Pediciidae). 658 records from Ravensthorpe Range survey data. 28 records from Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia. 26918 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 5 records from Schulinnenhöfe (Gelsenkirchen). 160 records from Wirbach-Taubental (Bad Blankenburg). 2 records from New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region. 215 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 180988 records from LSUMZ Birds Collection. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 5865 records from Auburn University Museum of Natural History Mollusks. 13 records from Description of two new Calicnemia from Vietnam and central Laos with notes on their congeners in Vietnam (Odonata: Platycnemididae). 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 1 records from A new species of mite in the genus Ernogamasus Athias-Henriot, 1971 (Parasitiformes: Parasitidae). 2 records from Notes on the genus Gargela (Lepidoptera: Crambidae) ı with descriptions of two new species from China. 12 records from Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 105 records from Occurrence of mammalia relicts at site Burghöhle Dietfurt. 37 records from New and poorly known Meligethes Stephens from China, with bionomical data on some species (Coleoptera: Nitidulidae: Meligethinae). 117 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 11130 records from Wikiplantbase #Sicilia. 1884 records from Database of Australasian Vertebrate Occurrences. 8 records from Review of the aquatic Hemiptera from Cephalonia, with a checklist for the Ionian Islands, Greece (Heteroptera: Gerromorpha, Nepomorpha, Leptopodomorpha). 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 1 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 250 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 1 records from dust metagenome Raw sequence reads. 27988 records from Bird records for Argyll for the years 2002 and 2003. 4034 records from nsmk_fish_biodiversity_2019. 5335 records from Ibaraki Nature Museum, Fish collection. 6 records from New records of two endemic troglobitic and threatened arachnids (Amblypygi and Opiliones) from limestone caves of Minas Gerais state, southeast Brazil. 22190 records from Marine Biological Sample Database, JAMSTEC. 26025 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 18 records from A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps. 3 records from Tobrilus saprophagus sp. n. and Epitobrilus interstitialis sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 874 records from The Living Murray Fish data. 2 records from Description of the puparium of Hermetia pulchra (Diptera: Stratiomyidae) from Brazil. 252 records from CNIN/Tipos Coleoptera. 15394 records from Carabidae records for Britain to 2014. 198 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 78 records from A checklist of Leiodidae (Coleoptera: Staphylinoidea) of Iran. 493 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 5 records from Additional new species of the genus Obolopteryx Cohn et al. 2014 (Ensifera: Tettigoniidae) from Northeastern Mexico. 196 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 653 records from SANBI: DNA Banking(1987-2011). 13983 records from Naturalis Biodiversity Center (NL) - Mammalia. 46265 records from Bacterial Diversity in the East China Sea. 2082 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 3 records from Taxonomy of deep-water tetillid sponges (Porifera, Demospongiae, Spirophorina) from Brazil, with description of three new species and new characters. 3 records from New Baltic amber leafhoppers representing the oldest Aphrodinae and Megophthalminae (Hemiptera, Cicadellidae). 50 records from Looking again at the forelimb of Tyrannosaurus rex. 18 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 357 records from Royal Saskatchewan Museum - Ichthyology Collection. 981 records from Monitoreo de la ocupación del Oso Andino Tremarctos ornatus en el Parque Nacional Natural Chingaza 2010. 1 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 92 records from Nottekanal, Klasse 7 - 10. 34 records from Taxonomic review of the moth family Thyatiridae (Lepidoptera) from Yunnan province, China. 6 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 13 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 34 records from Amoeboid protists isolated from ancient Siberian permafrost. 5923 records from Australian Coral Ecoregions. 88 records from A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group). 12 records from Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera Erebidae, Arctiinae) from China. 1289 records from A comparison of microbial community composition in four contrasting sediments in the Celtic Sea. 8 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 10 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 1809 records from BenthosChukchiFN762_1976_Falk5. 28 records from Face Biting on a Juvenile Tyrannosaurid and Behavioral Implications. 575 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 6 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 237 records from Capercaillie national surveys. 1 records from Description of two new Homoeocera Felder from Guatemala and Mexico (Lepidoptera, Arctiidae, Arctiinae, Euchromiini). 63 records from Marine gastropod distribution from patagonian shallow waters. 1 records from Two new species of Tenuipalpus Donnadieu, 1875 (Acari: Trombidiformes: Tenuipalpidae) from Iran. 88 records from Mycological collection of the National Museum. 10 records from Salticidae (Arachnida: Araneae) of New Caledonia: Genus Corambis Simon, 1901. 4 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 9 records from Five new species of Candoninae (Crustacea, Ostracoda) from the alluvial valley of the Upper Paraná River (Brazil, South America). 4 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 15458 records from SIO Benthic Invertebrate Collection. 1 records from Two new species of obligatory termitophilous rove beetles from Brazil (Coleoptera: Staphylinidae: Termitomorpha Wasmann). 341 records from DASSH Data Archive Centre volunteer survey data. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 121 records from BIRDRACE Immerwiederhopf. 7 records from Collection Malakologie - SMNG. 41 records from Rocky-intertidal cheilostome bryozoans from the vicinity of the Sesoko Biological Station, west-central Okinawa, Japan. 1721 records from Phytoplankton data collected from the Black Sea during November 1957 (Cruise 2). 2 records from New Cretaceous soldier beetle (Cantharidae) from Burmese amber with preserved coloration on the elytra. 440 records from Antarctic and Subantarctic Asteroid zoogeography. 2 records from New species and records of Omaliini from East Asia (Coleoptera: Staphylinidae: Omaliinae). 1300 records from Data from vegetation plots at Atiquipa, Southern Peru. 53 records from Revision of the genus Dinotoperla Tillyard, 1921 (Plecoptera: Gripopterygidae) using morphological characters and molecular data: Establishes two new genera, three new species and updates the larval taxonomy. 17 records from Chapter 7: Linnaean Plant Names and their Types (part Z). 54 records from Weidegebiete in der Selzrenaturierung. 60 records from A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research. 1 records from Lampetra soljani, a new brook lamprey from the southern Adriatic Sea basin (Petromyzontiformes: Petromyzontidae). 2916 records from Bacterial community dynamics during polysaccharide degradation at contrasting sites in the Southern and Atlantic Oceans. 3 records from A new species of Tambitnotia from Peru, with the first reported female of the genus (Lepidoptera: Tortricidae: Olethreutinae). 2 records from A new large and colourful species of the genus Doto (Nudibranchia: Dotidae) from South Africa. 5 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 7 records from Review Of The Species Of Conomorium Masi (Hymenoptera: Pteromalidae). 4 records from A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini). 304 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 1 records from A new species of Paraproto (Crustacea: Amphipoda) from southern New SouthWales, Australia. 3672 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 2 records from Two new species of Leptarma (Decapoda, Brachyura, Sesarmidae) from the Western Indian Ocean with notes on their phylogeny. 26 records from The caddisfly genus Protoptila in Costa Rica (Trichoptera: Glossosomatidae). 2 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 2 records from Rediscovering Anhanga: redescription and considerations on its taxonomic placement (Hemiptera: Heteroptera: Pentatomidae). 17 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1066 records from Territorial Andes Occidentales - Densidad poblacional VOC subsistema cámaras trampa, 2018. 8 records from A review of the species of Anaspis (s. str.) similar to A. nigripes Brisout and A. apfelbecki Schilsky, with the description of three new species (Coleoptera: Scraptiidae). 2 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 1 records from A new subspecies of Zamenis hohenackeri (Strauch, 1873) (Serpentes: Colubridae) based on morphological and molecular data. 31 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 1 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 424 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 29 records from Waldwiese. 2 records from Données taxonomiques et éthologiques nouvelles sur quatre espèces de Cigales du Sud thaïlandais (Rhynchota, Cicadoidea, Cicadidae). 10 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 12 records from Unexpected species diversity in electric eels with a description of the strongest living bioelectricity generator. 8 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 2 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 4 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 169 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 271 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 2 records from Two new species of the genus Crangonyx Bate, 1859 (Amphipoda: Crangonyctidae) from the St. Marks River Basin with notes on the “ Crangonyx floridanus complex ”. 81 records from Neotropical Acanthoderini (Coleoptera, Cerambycidae, Lamiinae): Synonymies and new status in some genera, new species, transferences and new distributional records. 1 records from A contribution to the revision of Adorodocia Brenske (Coleoptera: Scarabaeidae: Rutelinae: Adoretini): a new peculiar species from Ankaratra, Madagascar. 10 records from A new species of Eidmanacris Chopard, 1956, with notes on its distribution in Brazilian caves (Phalangopsidae, Luzarinae). 10 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 20 records from Truchas Mexicanas. 50 records from Flora und Fauna im Brexbachtal. 11 records from Late Cretaceous dinosaurs from the Denver Basin, Colorado. 13646 records from Senckenberg - CeDAMar Resource. 898985 records from MICROBIS database. 51 records from Marine metagenome ICM_VAG. 6 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 3 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 123 records from Birdrace-Professorenteam-Münster. 3 records from Ontario Breeding Bird Atlas 1981-1985. 2 records from Holorchis castex n. sp. (Digenea: Lepocreadiidae) from the painted sweet-lips Diagramma pictum (Thunberg, 1792) (Perciformes: Haemulidae) from New Caledonia. 2 records from Xenicola brauni sp. n., a new katydid species (Orthoptera: Tettigoniidae: Phaneropterinae) from the Atlantic Forest, southeastern Brazil. 21 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 11 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 1180 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 3 records from A new genus with three new species of free-living marine nematodes of the subfamily Desmodorinae (Nematoda: Desmodoridae), from the continental shelf off northeastern Brazil. 1 records from Swiss National Orthoptera Databank. 47 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 334 records from Santa Barbara Channel cruise SBDOM11 bacterioplankton 16S rDNA. 2 records from Morphology and phylogenetic analysis of two new species of deep-sea golden gorgonians (Cnidaria: Octocorallia: Chrysogorgiidae) from seamounts in the Western Pacific Ocean. 1579 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 150 records from Steinbruch Mainz-Weisenau. 1016 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 6 records from Pristipomoides amoenus (Snyder 1911), a valid species of jobfish (Pisces, Lutjanidae), with comparisons to P. argyrogrammicus (Valenciennes 1832). 5 records from New bobtail squid (Sepiolidae: Sepiolinae) from the Ryukyu islands revealed by molecular and morphological analysis. 119 records from Fauna y flora del municipio de Lipa, Arauca. 7 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 2 records from Japanese Pseudosmittia Edwards (Diptera: Chironomidae). 828 records from Insect specimens of Natural History Museum, Kishiwada City. 14 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 38 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Corvidae. 5 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 11 records from Chenopodium. 3 records from A new species of snook, Centropomus (Teleostei: Centropomidae), from northern South America, with notes on the geographic distribution of other species of the genus. 31 records from Nationalpark Harz Schul-AG Braunlage. 965 records from Diatom distribution in Madeira Island streams (Portugal). 21 records from Tyrannosaurus And Torosaurus, Maestrichtian Dinosaurs From Trans-Pecos, Texas. 1 records from Naiadacarus sidorchukae sp. n. (Acariformes: Acaridae) from Western Siberia closely related to a North American species, with a new generic synonymy. 536 records from NEW-1. 7 records from Review of the Neotropical spider wasp subgenus Anoplius (Dicranoplius) Haupt (Hymenoptera: Pompilidae), new comb.. 5 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 7 records from Description of Paracymbiomma gen. nov., a new genus of prodidomid spiders from the Neotropical region (Araneae: Prodidomidae) including a new troglobite species. 3636 records from Fish: Records for Kent.. 38 records from Was lebt in der Brutzwiese?. 1 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 12 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 2001 records from Marine sediment Raw sequence reads. 1 records from Croton calcareus: a new species of dragon’s blood (Euphorbiaceae) from dry forest in the state of Chiapas, Mexico. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 24 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 7 records from Family, generic and species synonymies of recently published taxa of ghost shrimps (Decapoda, Axiidea, Eucalliacidae and Ctenochelidae): cautionary tales. 1 records from On the Chilopoda from Turkey. 36 records from Wichita State University Collection. 4 records from New and interesting species of sacculonotic Haplozetidae (Acari, Oribatida, Haplozetidae) from Indonesia. 62 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 33 records from Taxonomic status of maskrays of the Neotrygon kuhlii species complex (Myliobatoidei: Dasyatidae) with the description of three new species from the Indo-West Pacific. 28 records from Halophila stipulacea in the Caribbean Sea. 58 records from Annotated catalogue of the click-beetle subfamily Tetralobinae (Coleoptera: Elateridae). 156 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 2 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 215 records from Taxonomic revision of the flavopalliata species group of Signiphora (Hymenoptera: Signiphoridae). 8158 records from Dark ocean microbial diversity. 3 records from Chemistry supports the identification of gender-specific reproductive tissue in Tyrannosaurus rex. 8 records from A new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae Ortmann, 1896) from Yunnan Province, China. 5 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 3 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 218 records from pbzt_insect_biodiversity. 28618 records from Insect specimens of Himeji City Science Museum. 4 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 2412 records from Ohio University Invertebrate Paleontology Collection. 23 records from Metagenetic analysis of copepod community in the tropical and subtropical Pacific. 8 records from NZCS Upper Tapanahony Expedition 1991. 1 records from Subterranean millipedes (Diplopoda) of the Iberian Peninsula. 7 records from A new subspecies of Delias clathrata Rothschild, 1904 and records of other Delias species occurring on Mount Hagen, Papua New Guinea (Lepidoptera: Pieridae, Pierinae). 1 records from Oppia nitens. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 1 records from Description of the female of Chelis ferghana Dubatolov, 1988, an endemic moth species of the Tien Shan Range in Central Asia (Lepidoptera: Erebidae Arctiinae). 3 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 8 records from Oxynoemacheilus hazarensis, a new species from Lake Hazar in Turkey, with remarks on O. euphraticus (Teleostei: Nemacheilidae). 14 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 29 records from An annotated catalogue of the gamasid mites associated with small mammals in Asiatic Russia. The family Haemogamasidae (Acari: Mesostigmata: Gamasina). 28 records from Occurrence of mammalia relicts at site Bettelküche. 33318 records from BrioCAT: Banco de datos de los briòfitos de Cataluña. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 3 records from DD_cyano Targeted loci environmental. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 11 records from Types of Thyatirinae (Lepidoptera: Drepanidae) in the collection of the Zoological Institute of the Russian Academy of Sciences. 5 records from Thalassironus filiformis sp. nov. (Nematoda, Enoplida) from the South China Sea. 128 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 1 records from Oribates fusifer. 2 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 22 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 8 records from Phoronida - SMF. 258 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 25 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 75 records from Nemertini - SMF. 2 records from A novel Enterostomula (Platyhelminthes, Prolecithophora) species from two brackish lakes in Japan. 2 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 12 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 1 records from On the Chilopoda from Turkey. 125377 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 1 records from Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran. 203 records from Upper Silesian Museum, Bird Collection. 1 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 16 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 3 records from New synonymies in the plant bug family Miridae (Hemiptera: Heteroptera) from Northern China. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 4207 records from CASES2003_2004. 29 records from Hemmerder Schelk (Unna). 1139 records from Shellfish (MNHM-MS). 63 records from Fife Nature Records Centre combined dataset. 138 records from First records of 31 species of butterflies and moths (Lepidoptera) in Cameroon, with remarks on their elevational ranges. 37 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 1 records from Notes on the genus Kosmiomiris Kirkaldy (Hemiptera: Miridae: Hyalopeplini) with description of a new species. 10 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 3 records from First record of Gauguin's blunt-nose lizardfish, Trachinocephalus gauguini Polanco, Acero & Betancur 2016 (Teleostei: Synodontidae) outside the Marquesas Archipelago. 6116 records from Muséum de Nîmes. 4 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 2304 records from Ridge to Reef Marine Monitoring of Fanga'uta Lagoon, Tonga, October 2017. 215 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 465 records from Hyperbenthos community in the salt marsh of Saeftinghe in 1990 and 1991. 16 records from jamaica_invasive_alien_species. 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 367 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 6 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 15 records from Two new deep-water species of the genus Thorogobius (Teleostei: Gobiidae) from the upper continental slope of the Eastern Central Atlantic. 8 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 2 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 2 records from A new South American species of Palaeophileurus Kolbe (Coleoptera: Scarabaeidae: Dynastinae: Phileurini). 27 records from Review of Neocynorta Roewerı 1915 with two new generic synonymies (Opiliones: Gonyleptoidea: Cosmetidae). 1 records from A new tardigrade species of the genus Neostygarctus Grimaldi de Zio et al., 1982 (Tardigrada, Arthrotardigrada) from the Great Meteor Seamount, Northeast Atlantic. 272 records from BIRDRACE Niederlausitz-Team. 3512 records from Cnidaria. 309 records from Chapter 7: Linnaean Plant Names and their Types (part T). 380 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from A revision of the genus Boroecia Poulsen 1973 (Ostracoda, Halocypridae) with the descriptions of three new species. 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 60 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 64 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 1 records from Description of Pratylenchoides ojcowensis sp. nov. (Nematoda: Merlinidae) from Polish Jurassic Highland. 13459 records from Plant (JNHM-PL). 7455 records from Botanic Garden of the Finnish Museum of Natural History. 7657 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 901 records from The Masao Oita Insect Collection of The University Museum, The University of Tokyo. 364 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 12 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 1619 records from LACM Invertebrate Paleontology. 3 records from Boraginaceae (Cynoglossum cherangauiense). 1 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 10386 records from Ice Wedge Polygon. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 1 records from Ptilophora variabilis Hartig, 1968, bona species, and description of Ptilophora nebrodensis sp. n. from Sicily (Lepidoptera, Notodontidae). 4 records from Tortonian teleost otoliths from northern Italy: taxonomic synthesis and stratigraphic significance. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 127 records from Collection Ephemeroptera - SMF. 102 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 16 records from Occurrence of mammalia relicts at site Pestera lui Climente I. 242 records from FBIP: Identification of polychaetes used as bait. 2007 records from Denver Museum of Nature & Science - Entomology. 1 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 2 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 42 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 16506 records from Database for alien invasive plants occurrences in Germany. 15 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 685 records from Capture of Primary Biodiversity Data for West African Plants. 25 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 31 records from Revision of the amphiamerican genus Mysidium Dana, 1852 (Crustacea: Mysida: Mysidae), with descriptions of two new species and the establishment of two new subgenera. 1 records from Arthropoden aus südostalpinen Höhlen.. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 9 records from Taxonomy of Euschizomerus Chaudoir 1850 (Coleo
Keywords: GBIF; biodiversity; species occurrences